(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
Retinoids, derivatives of vitamin A, play a fundamental role in modern medicine, particularly in dermatology and oncology. Acting at the cellular level, they regulate differentiation, proliferation, and apoptosis (Kang et al. 2021). Unlike topical formulations, systemic retinoids exert effects throughout the body after absorption into the bloodstream. Because of their profound biological activity, they are employed in the treatment of severe and refractory diseases such as nodulocystic acne, psoriasis, inherited keratinization disorders, and certain malignancies (Siegenthaler et al. 2019; Zouboulis 2020).